Formulation and Evaluation of Transdermal Gel From Bajakah Extract (Spatholobus Littoralis) as an Anti-Inflammatory Agent - Radiat Warji; Hasyrul Hamzah (CV. Publikasi Indonesia, 2026)
The objectives of this study were threefold: (1) to formulate Bajakah Tampala extract (Spatholobus littoralis) into a stable transdermal gel with variations in gelling agent and penetration enhancer concentrations; (2) to evaluate the physical characteristics of the resulting transdermal gel; and (3) to determine the anti-inflammatory efficacy of the gel in a white mouse model. The study hypothesizes that there is no significant difference in anti-inflammatory activity between the transdermal gel and the negative control, and that the gel formulation does not fully meet all standard evaluation parameters, such as thickness. A laboratory experimental design with pre-test and post-test approaches was employed using twenty-two male white rats (Rattus norvegicus), aged 2–3 months and weighing 200–250 grams. Data were analyzed using the paired t-test. Results indicated that the transdermal gel exhibited good and stable physical characteristics, with a homogeneous texture, skin-compatible pH (5.2–6.2), and the ability to withstand over 400 folds without damage. Formulas containing penetration enhancers (F2 and F3) demonstrated superior pH stability and weight uniformity compared to F1. In vivo testing revealed that F2 and F3 reduced edema to 0.30–0.31 mL, nearly matching the positive control (diclofenac sodium, 0.45 mL). These findings suggest that the incorporation of penetration enhancers significantly improves the gel’s ability to deliver Bajakah extract and suppress inflammatory responses.